Characterization and Photocatalytic Activity of TmVO4 Prepared by Hydrothermal Method. Issue 1 (2nd September 2021) - Zhou, Yifan; Chen, Haifeng; Hou, Ruipeng; Zhang, Liqin; Sun, Shouquan; Tang, Peisong
Abstract: Using thulium oxide, nitric acid, ammonium metavanadate and citric acid as main raw materials, TmVO4 was successfully prepared by hydrothermal method. TmVO4 samples were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), thermogravimetry differential scanning calorimetry (TG-DSC), and Fourier transform infrared spectroscopy (FT-IR). Taking methyl orange solution as simulated sewage, the effects of synthesis temperature and illumination time on the photocatalytic activity of TmVO4 were studied. The results show that pure tetragonal zircon TmVO4 samples can be obtained under hydrothermal conditions of 120 °C to 180 °C. The sample prepared at 140°Chas uniform grain size, and the average grain size is about 50 nm. Under ultraviolet light illumination for 30 min, the degradation rate of 10 mg/L methyl orange can reach more than 77% in the presence of TmVO4 . The photocatalysis experiment indicated that TmVO4 has good photocatalytic degradation activity for methyl orange.